-3c-12=-5+6

Simple and best practice solution for -3c-12=-5+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3c-12=-5+6 equation:


Simplifying
-3c + -12 = -5 + 6

Reorder the terms:
-12 + -3c = -5 + 6

Combine like terms: -5 + 6 = 1
-12 + -3c = 1

Solving
-12 + -3c = 1

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + -3c = 1 + 12

Combine like terms: -12 + 12 = 0
0 + -3c = 1 + 12
-3c = 1 + 12

Combine like terms: 1 + 12 = 13
-3c = 13

Divide each side by '-3'.
c = -4.333333333

Simplifying
c = -4.333333333

See similar equations:

| 25+2r=5(t+2) | | X+y+4y+x=180 | | 4(-2x-3)+2x=36 | | x^3+2x^2-18x=0 | | 250/2=x+5 | | 2(0.7)(0.7+5)= | | 12a-15=18a+1 | | -x-4=3x-52 | | -6t+-7=7 | | 2r(0.7+5)= | | 4x+3-8x+1=-5x+9 | | 6(3x+5)-9x=75 | | 12-3y=16-5y | | 3-5=7n+11 | | 2x+7+(2x+6)+2x=2x+(2x)+(3x)+7 | | -20=0.1x-0.5x | | 1/2(2/4) | | 188=32x+10(6) | | 2/3(12-14)=2 | | m+7+8=-28 | | x^3+9x^2+8x+72=0 | | 3(x+7)-3=54 | | 10+5-1-5b=15b+3 | | m+7+8=28 | | .20x+.25(70)=36.5 | | 2=6(2a+2) | | -4x+10=-2x+2 | | -3(2-4x)=18 | | m+4+9=-23 | | m+4+9=23 | | 2/3(-42+49)=2 | | 6x+24=10x-20 |

Equations solver categories